Ayurvedic Management of Yakrit Vidradhi (Liver Abscess) – A Case Report - Varsakiya, Jitendra; Kathad, Divyarani; Kumari, Ritu; Nayak, Sourava (International Research Journal of Ayurveda & Yoga, 2023)
The liver abscess is the most frequent visceral abscess caused by a parasite or bacterial infection in low and middle-income countries. A liver abscess can cause fever, chills, night sweats, malaise, nausea or vomiting, right shoulder ache, right upper quadrant pain, cough, dyspnea, anorexia, etc. A 20 years old male patient presented with symptoms of fever, chills, malaise, right shoulder pain, and right upper quadrantpain.The patient was treated with Virechan Karma (therapeutic purgation) followed by oral Ayurvedic medicines such as Varunadi Kwatha, Kanchanar Guggulu, and Aarogyavardhini Vati. Pathya apathy (wholesome-unwholesome diet) based on Ayurveda perspectives was also advised to the patient. The total duration of the treatment was four months, and follow-up was done for one month. Improvement was assessed based on relief in the symptoms and abdomen USG. Complete relief in all symptoms was noted after completion of the treatment. The USG findings revealed a reduction in hypoechoic lesion to size 5.1*5.1 cm with calcified margins in the right lobe segment VIII of the liver. Any complications or adverse events due to treatment were not observed during the treatment period. This case report demonstrates the effectiveness of Ayurvedic approaches in managing Liver abscesses.